Nasihat Al-Mulk: Pemikiran Politik Raja Ali Haji Perspektif Etik - Alimuddin Hassan Palawa (Proceedings of Annual Conference for Muslim Scholars, 2018)
The image of a good ruler is always to meet the needs of his people and think about the life (fate) of his people. With this kind of leadership behavior, the people will be prosperous and peaceful and people always obey it because in the hearts of the people terpatri fame the wisdom of its leader leaders. In addition, a good ruler is not indulging his lust, avoiding disgraceful nature and attitude and avoiding unfavorable world life. Furthermore, Raja Ali Haji mentioned that the good ruler will build facilities and infrastructure in support of the achievement of the welfare of the community, reducing the occurrence of slander in society, religion maintained and custom preserved, education is noticed, law is enforced and the community is finally close to God. In the section of Raja Ali Haji detailing the characteristics of a ruling ruler, which reigns with "whip" (iron hand), has a rough temperament and has no shame. In addition, the ugly ruler does not pay attention to the welfare and tranquility of his people, especially for the common people and the poor. The image of the ugly ruler is like indulging his lust, pursuing a less than decent world life. Furthermore, the sign of the ruler is not good is to ignore the construction of facilities and infrastructure of community life, religious life abandoned and customs and culture is not maintained and society is far from God.The image of the ruler is bad and is reflected in his attitude towards upholding the main principles of power. Principles of power referred to, as there is a small treatise Raja Ali Haji, Muqaddimah fī al-Intiẓām, consists of the principles of justice, the principle of deliberation, and the principle of equality. A good ruler will uphold justice, deliberation and equality among the people. On the contrary, bad rulers are unjust, authoritarian and discriminatory.